PELATIHAN MANAJEMEN KEUANGAN KELUARGA UNTUK MENINGKATKAN KESEJAHTERAAN MASYARAKAT DESA (Holistic Journal of Management Research, 2020)
Consumerism is a condition for someone who has a tendency to consume a good or service. Expenditures resulting from the use of a good or service are normal activities if they pay attention to their suitability with financial conditions or income. Expenditure idealism is a portion of the income received, so that it does not exceed the ability of financial income. This is a problem that is often experienced by people such as in Desa Notog Kec. Patikraja Kab. Banyumas. Most of the people have high income but cannot manage their finances properly so that they always result in spending that exceeds their income capacity. The purpose of this service activity is the introduction of technology-based family financial management training for housewives through hands-on training and practice using family financial management application technology that can be accessed via smartphones. This training was carried out in order to overcome family financial problems that always occur in the community of Notog Village, Patikraja District, Banyumas Regency because they are not careful in managing monthly financial income and expenditure. Activities are carried out by using the family financial management theory training method as well as direct practice of implementing the training using an application on a smartphone. The result of this activity is that the community better understands the concept of expenditure based on family income so that they no longer experience financial difficulties. The output of this activity is an application that can be used by the community easily and supports family financial management. Based on the application of this system, the people of Notog Village no longer experience financial difficulties because monthly income can be managed in a structured manner for savings (investment) and daily expenses. The suggestion for this service activity is that it is better to differentiate application systems that do not only use smartphones, because some people are not very familiar with technology, so they need other alternatives that cover all levels of society.